2021
DOI: 10.1111/jen.12944
|View full text |Cite
|
Sign up to set email alerts
|

Anoplophora glabripennis: Host choice, oviposition and performance of new hatched larvae on ‘resistant’ poplar species

Abstract: Most western regions of China are arid or semi-arid. To reduce encroachment by sandstorms in these areas, tens of thousands of forest belts have been established since the 1970s. The majority of these forests are comprised of different varieties or clones of poplar which are tall, fast-growing and resistant to environmental stress (Lv et al., 2000). To date, poplar is still the first choice when planting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Moreover, our result prompts a new question, i.e., should we plant lure trees near relatively resistant trees (or non-host tree)? Different tree species exhibit different levels of resistance to ALB, 8,9,44 and some host tree species have been recommended for use as lure trees to be planted in mixed forests of relatively highly resistant poplar. [45][46][47] In this scenario, they might encourage ALB oviposition on relatively resistant poplars, then some ALB individuals might develop the counter-defenses ability and finally break the defense system of these resistant poplars.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, our result prompts a new question, i.e., should we plant lure trees near relatively resistant trees (or non-host tree)? Different tree species exhibit different levels of resistance to ALB, 8,9,44 and some host tree species have been recommended for use as lure trees to be planted in mixed forests of relatively highly resistant poplar. [45][46][47] In this scenario, they might encourage ALB oviposition on relatively resistant poplars, then some ALB individuals might develop the counter-defenses ability and finally break the defense system of these resistant poplars.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Populus deltoides 'Shalinyang' (PdS), which can grow in north-western China, is attractive to ALB adults for oviposition but that the resulting offspring do not survive subsequent development. 8,9 This resistant variety has proved to be promising for regulating ALB populations. 8,9 Volatiles emitted by host plants can mediate interspecific interactions between plants and insects.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations